2021
DOI: 10.1002/cnr2.1367
|View full text |Cite
|
Sign up to set email alerts
|

ModraDoc006, an oral docetaxel formulation in combination with ritonavir (ModraDoc006/r), in metastatic castration‐resistant prostate cancer patients: A phase Ib study

Abstract: Background: ModraDoc006 is an oral formulation of docetaxel, which is co-administered with the cytochrome P450 3A4 and P-glycoprotein inhibitor ritonavir (r): ModraDoc006/r. Weekly treatment with ModraDoc006/r had been evaluated in phase I trials in patients with different types of advanced solid tumors, but up to this point in time not in patients with metastatic castration-resistant prostate cancer (mCRPC).Aim: We assessed safety and pharmacokinetics (PK) of ModraDoc006/r to establish the recommended phase 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The plasma AUC of docetaxel could be enhanced 7.3-fold with coadministration of ritonavir, whereas the plasma AUC of paclitaxel showed a 2.5-fold enhancement . These preclinical results have been used as a basis to develop oral administration regimens for paclitaxel and especially docetaxel, which are currently tested and optimized in humans. ,, Currently, an oral docetaxel formulation (ModraDoc006) in combination with ritonavir is tested in clinical trials. , Taking all results of the present study together, they form a good starting point to test an oral cabazitaxel formulation in combination with ritonavir in a small patient population. An oral drug formulation is more patient-friendly, and besides it allows metronomic chemotherapy .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The plasma AUC of docetaxel could be enhanced 7.3-fold with coadministration of ritonavir, whereas the plasma AUC of paclitaxel showed a 2.5-fold enhancement . These preclinical results have been used as a basis to develop oral administration regimens for paclitaxel and especially docetaxel, which are currently tested and optimized in humans. ,, Currently, an oral docetaxel formulation (ModraDoc006) in combination with ritonavir is tested in clinical trials. , Taking all results of the present study together, they form a good starting point to test an oral cabazitaxel formulation in combination with ritonavir in a small patient population. An oral drug formulation is more patient-friendly, and besides it allows metronomic chemotherapy .…”
Section: Discussionmentioning
confidence: 68%
“…10 These preclinical results have been used as a basis to develop oral administration regimens for paclitaxel and especially docetaxel, which are currently tested and optimized in humans. 9,36,37 Currently, an oral docetaxel formulation (ModraDoc006) in combination with ritonavir is tested in clinical trials. 19,36 Taking all results of the present study together, they form a good starting point to test an oral cabazitaxel formulation in combination with ritonavir in a small patient population.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future analyses demonstrating ABCB1 amplification as a biomarker of primary resistance to either taxane for mCRPC would allow for the consideration of alternative treatment strategies, including the selection of patients for co-administration of an inhibitor of ABCB1/P-glycoprotein. These inhibitors have shown promising activity in reversing taxane resistance in vitro [37][38][39], and ritonavir is being used as a P-glycoprotein inhibitor in combination with oral docetaxel to increase the bioavailability of the taxane [40]. Because prior clinical trials of ABCB1/P-glycoprotein inhibitors have demonstrated notable toxicities, while novel inhibitors are in development [41], the ability to select for patients most likely to benefit from these agents is potentially clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, how to improve poor oral bioavailability is the key to the development of oral chemotherapeutic agents. Docetaxel as the rst line antitumor agent was currently used for prostate cancer, non-small cell lung cancer (NSCLC) [2][3]. The recommended dose schedule was intravenously administered decetaxel every 3 weeks, which was restricted by myelosuppression in clinic.…”
Section: Introductionmentioning
confidence: 99%